2017
DOI: 10.1249/mss.0000000000001100
|View full text |Cite
|
Sign up to set email alerts
|

Step-Based Physical Activity Metrics and Cardiometabolic Risk

Abstract: Purpose To catalog the relationships between step-based accelerometer metrics indicative of physical activity volume (steps/day, adjusted to a pedometer scale), intensity (mean steps/min from the highest, not necessarily consecutive, minutes in a day; peak 30-min cadence) and sedentary behavior (percent time at zero cadence relative to wear time; %TZC) and cardiometabolic risk factors. Methods We analyzed data from 3388 20+ year-old participants in the 2005-2006 National Health and Nutrition Examination Surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
60
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 42 publications
(71 reference statements)
4
60
0
1
Order By: Relevance
“…A study investigating pedometer's accuracy according to their position worn at various walking speeds showed that at all positions, pedometers generated significant errors at slow speeds and therefore cannot be used reliably to evaluate the amount of physical activity for people walking slower than 0.6 m/s (2.16 km/h, or 1.24 mph) [15]. Regardless of that, pedometers are used in many areas such as primary care [16] increasing physical activity and stress management [17,18] decreasing cardiovascular risk factors [19] and adolescents [20]. RT6 and pedometer results were not found significantly correlated in our study.…”
Section: Discussionmentioning
confidence: 99%
“…A study investigating pedometer's accuracy according to their position worn at various walking speeds showed that at all positions, pedometers generated significant errors at slow speeds and therefore cannot be used reliably to evaluate the amount of physical activity for people walking slower than 0.6 m/s (2.16 km/h, or 1.24 mph) [15]. Regardless of that, pedometers are used in many areas such as primary care [16] increasing physical activity and stress management [17,18] decreasing cardiovascular risk factors [19] and adolescents [20]. RT6 and pedometer results were not found significantly correlated in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, its inclusion in commercially available physical activity trackers has popularized its use, as it is now commonly used in weight loss or fitness programs. If an accelerometer is used to guide exercise in ESLD patients, it is important to note that walking at a pace of 100 steps/minute corresponds to moderate‐to‐vigorous exercise intensity . Thus, to recommend bouts of 30 minutes of exercise, patients should achieve 3000 steps during that time frame to maintain proper exercise intensity.…”
Section: Future Directionsmentioning
confidence: 99%
“…If an accelerometer is used to guide exercise in ESLD patients, it is important to note that walking at a pace of 100 steps/minute corresponds to moderate-tovigorous exercise intensity. (85) Thus, to recommend bouts of 30 minutes of exercise, patients should achieve 3000 steps during that time frame to maintain proper exercise intensity. When combining NEAT and exercise, an equivalent of 7000-10,000 steps/day is expected.…”
Section: Future Directionsmentioning
confidence: 99%
“…Recent studies using objective measures of physical activity, such as accelerometers, have mostly examined associations of health with total duration of physical activity. These studies found more physical activity141516 or MVPA1517 to be associated with favorable cardiometabolic outcomes1819 and better motor1516 and cognitive1417 function. There is also some evidence to suggest that time spent in both short and long MVPA bouts is associated with better cardio-metabolic health202122 and reduced risk of multimorbidity23.…”
mentioning
confidence: 97%